Enhanced electric and magnetic properties of (BiLi)1/2(Fe2/3W1/3)O3 multiferroic as compared to BiFeO3. Issue 5 (April 2016) - Ahmed, Suhel; Barik, Subrat Kumar
Abstract: Very low electric and magnetic moments are the two major disadvantages which restrict the practical applications of BiFeO3 . We have doped Li + and W 6+ in Bi 3+ and Fe 3+ site respectively to overcome the limitations of BiFeO3 . Pure BiFeO3 and (BiLi)1/2 (Fe2/3 W1/3 )O3 (BLFWO) are synthesized by a solid-state reaction technique. The samples are characterized by X-ray diffractometer, LCR meter, P – E loop tracer, vibrating sample magnetometer and dc resistivity setup to understand their different properties. Dielectric and impedance studies of the samples are measured at different frequency (10 2 –10 6  Hz) in a wide temperature range (30–375 °C). Due to co-doping in pure BFO the remnant polarization and remnant magnetization are enhanced and thus BLFWO may show large industrial utility.